The Eurosystem and the art of central banking - Gunnar Heinsohn; Otto Steiger (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2002)
The Eurosystem is the fifth decentralized system in the history of central banks. It consists of the European Central Bank (ECB) and twelve National Central Banks (NCBs) forming the European Monetary Union (EMU). The stark decentrality of this System is so little known that ubiquitous statements by high level Euro experts on its supposed similarity with other decentralized systems, like the former Bundesbank System and the existing Federal Reserve System, are met with no protest. A closer look on European documents and the balance sheet of the ECB reveals, however, that the ECB – far from being the monopoly supplier of central bank money – cannot set the refinancing conditions to credit institutions in EMU. The latter are determined by the Council of Governors of the European Central Banks, while the main refinancing operations are executed by the NCBs leaving to the ECB the role of vicarious agent. The ECB can neither control all types of securities accepted for the NCBs' credit operations nor is it able to act as the lender of last resort. Yet, every possible manoeuvre to make the ECB look like a central bank of the NCBs is relentlessly employed, most obviously in the design of the Euro banknotes, which are issued by the NCBs but carry only the imprint of the ECB.
Keywords: E58; 330; Zentralbank; Europäische Wirtschafts- und Währungsunion; Kritik; EU-Staaten; Lender of Last Resort